Risk Factors of Green Tobacco Sickness on Tobacco Farmers in Jember Indonesia - Anita Dewi Prahastuti Sujoso1,2, Tri Martiana3 , Santi Martini4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction. Green Tobacco Sickness (GTS) is a disease in the working population that is still not widely disclosed. GTS characterized by the main symptoms of nausea, vomiting, dizziness, excessive sweating, and occurs when in contact with wet tobacco. This research purpose is to assess the factors associated with the incidence of GTS in tobacco farmers in Jember, Indonesia. Methods. The research design is case control. Research variables are occupational factors and individual factors. Data analysis using binner logistic regression. Result and Discussion. The results stated that the variable influencing the case of GTS in tobacco farmers was the work period OR = 2,944, (CI 1,127-7,693) smoking status OR = 18,083 (CI 6.815-47,984) dermatosis complaints OR = 3,876 (CI = 1,238-12,138) and nutritional status was assessed with a BMI, OR = 2.643 (CI = 1.038-6.733). Farmers with a working period of working 18 years have a risk of 2,944 times GTS compared to farmers with a work period of <18 years. Farmers with smoking status have a risk of 18,083 times GTS compared to non-smoking farmers. Farmers who have dermatoses have a risk of 1,355 times GTS compared to farmers who do not have complaints of dermatosis. Farmers with an abnormal (overweight) BMI have a risk of 2,643 times GTS compared to farmers with a normal BMI. Conclusion. Factors that influence the GTS are age, sex, smoking status, complaints of dermatosis, nutritional status, and years of service. The findings of this study suggest that integrated promotive and preventive measures from both agricultural owners and first-rate health care providers need in the form of providing self-help to reduce direct contact with wet tobacco, healthy living behavior without smoking and maintaining nutritional status.